Optimasi Formula Sediaan Fast Disintegrating Tablet (FDT) Ekstrak Etanolik Herba Pegagan (Centella asiatica (L.) Urb.) - Agatha Budi Susiana Lestari; Achmad Fudholi; Akhmad Kharis Nugroho; Erna Prawita Setyowati (JURNAL ILMU KEFARMASIAN INDONESIA, 2018)
It has been proven that Centella asiatica (L.) Urb. herbs have an antioxidant activity that make it possible to used in preventing degenerative illness. Centella asiatica (L.) extract has been formulated to fast disintegrating tablet (FDT) dosage form. The aims of this study are to find the optimum formula of FDT of Centella asiatica (L.) Urb. The simplex lattice design method with 3 factors (which are mannitol as diluents, crospovidone as superdisintegrant and povidone as binder) and 2 levels of each was used. Centella asiatica (L.) Urb. extract was produce from maceration process using ethanol-water in ratio 75%:25% as a solvent. Direct compress method was used to produce the FDT. The results show that the optimum composition between excipients FDT formula could be reached, which fullfiled the physical properties parameter which are the hardness, friability and disintegration time of FDT.